Sanksi Tindak Pidana Korupsi oleh Pegawai Negeri dalam Prespektif Fiqih Jinayah - Yuli Rohmatul Hidayah (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2019)
The economic crises that hit Indonesia for a long time were caused by corruption. Corruption itself was the result of the absence of integrated control. Corruption is a crime, it is an abuse of authority. It has been known that the perpetrators are state officials who have